АНАЛІЗ ПЕРСПЕКТИВ РОЗВИТКУ ТЕЦ УКРАЇНИ В УМОВАХ ІНТЕГРАЦІЇ В ЗАГАЛЬНОЄВРОПЕЙСЬКИЙ ПРОСТІР - А.І. Замулко; М.О. Довгаль (Праці Інституту електродинаміки Національної академії наук України, 2023)
Modern heat and power plants (HPPs) face numerous challenges related to energy efficiency, the integration of renew-able energy sources, and environmental sustainability. The article examines the possibilities and prospects for the de-velopment of HPPs taking into account current trends and challenges. The main directions of HPP development include the integration of renewable energy sources (RES), the decentraliza-tion of energy systems, a focus on environmental sustainability, and the development of legislative and regulatory frameworks. These measures will contribute to the sustainable development of the energy infrastructure, ensuring en-ergy security, and improving environmental quality. Bibl.7, fig. 4, table.